Evolution of cooperation in a spatial structure with compensation mechanisms. (November 2017) - Sun, Peiyuan; Liu, Xuesong; Wang, Enze; He, Mingfeng; Pan, Qiuhui
Abstract: We study the evolution of cooperation by modeling interactional individuals with compensation mechanism on a two-dimensional square lattice. In this model, the payoff to cooperators is the same no matter what types their neighbors are, while the payoff to defectors depends on whether there exists cooperative neighbor. In addition, cooperators will obtain some compensation from the payoffs of defectors. We find that a larger compensation coefficient in the model leads to the higher cooperation, which means the compensation mechanism partly promotes cooperation. In addition, the simulation results suggest that decreasing either the payoff of defectors without cooperative neighbors or the payoff of defectors with cooperative neighbors will promote cooperation.